Work Readiness Based on the Social studies Dimension in Vocational School Students, Sambas Regency - Jumardi Budiman (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
This study aims to describe and analyzes the social work based on educational dimension at Vocational High School, Sambas in four dimensions: a) knowledge; b) skill; c) values and attitudes; d) the social act. The method used by researchers was a qualitative methodology descriptive. Technique data collection by direct communication of interviews was based on guidelines. Informants were students of class xii research that follow activities vocational internship. The data analysis technique used that is reduction data, presentation of data, and withdrawals conclusion. Based on research findings and process data can be expressed that eighth graders XII, Vocational High School have had the readiness to work if considered from four dimensions of social studies namely dimensions knowledge is shown understanding about the fact, students the concept and generalization; Dimensions of skill shown through the research skills thinking, skills skill participation social and conversation skills needed the work; dimensions and attitudes shown through the value of the substantive implanted to students through education and scores of formal and informal procedural useful as capital social participation in the work; The social act of dimensions is shown by student's ability in determining the decisions made and solutions to problems in a work environment.